Performance of CREAM Calorimeter: Results of Beam Tests - H. S. AHN; BAGLIESI, MARIA GRAZIA; J. J. BEATTY; BIGONGIARI, GABRIELE; A. CASTELLINA; J. T. CHILDERS; N. B. CONKLIN; S. COUTU; M. A. DUVERNOIS; O. GANEL; J. H. HAN; H. J. HYUN; et al. (Nuclear Physics B - Proceedings Supplements, 2006)
The Cosmic Ray Energetics And Mass (CREAM), a balloon-borne experiment, is under preparation for a flight in Antarctica at the end of 2004. CREAM is planned to measure the energy spectrum and composition of cosmic rays directly at energies between 1 TeV and 1000 TeV. Incident particle energies will be measured by a transition radiation detector and a sampling calorimeter. The calorimeter was constructed at the University of Maryland and tested at CERN in 2003. Performance of the calorimeter during the beam tests is reported.